Role of analyst following in the relationship between integrated reporting quality irq disclosure and cost of equity capital in developed markets - Sharif, Hazhar; Johari, Jalila (Horizon Research Publishing Corporation, 2022)
The study aims to examine the role of analyst following (AF) in the relationship between IR quality (IRQ) disclosures and implied cost of equity capital (ICC) in the developed market in Australia and New Zealand. The study also examined whether companies with higher-quality integrated reporting (IR) benefit from the cost of equity capital reduction. The main objective is to identify the role of AF in explaining the relationship between IRQ disclosure and ICC. Besides, the study highlighted the average effects of IR benefits, which increase when there is more information asymmetry between firms and investors. Furthermore, IR could play a bigger role (with greater information asymmetry) than cross-sectional tests. The study used a common sample of 100 top companies based on Standard and Poor's market capitalisation in Australia and New Zealand (2014-2016), with 870 observations of post-implementation IR. This study showed a significant, negative relationship between IRQ and the ICC with top companies in Australia and New Zealand. Also, the results showed that AF is a partial mediator in explaining the relationship between IRQ and the cost of equity capital. The findings also indicated that AF has a vital role in IRQ disclosures, associated with a subsequent reduction in the cost of equity capital in the developed market.